Colorimetric detection of hypochlorite in tap water based on the oxidation of 3, 3′, 5, 5′-tetramethyl benzidine1. Issue 10 (21st May 2015) - Guo, Yongming; Ma, Qinge; Cao, Fengpu; Zhao, Qiang; Ji, Xuewei
<x xml:space="preserve">Abstract</x> A simple method for the colorimetric detection of hypochlorite in tap water with good selectivity and sensitivity has been developed by utilization of the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine.